Sustaining e-caring leadership in a post-pandemic world - Joko Gunawan; Colleen Marzilli; Yupin Aungsuroch (Belitung Raya Foundation, Indonesia, 2022)
At the convergence of the “new normal” from the COVID-19 pandemic and the combination of caring, leadership, and technology, a new environment for organizational culture was formed. The injection of technology into how leaders provided care to their organization launched e-caring, and this is now considered a key in employee engagement and retention post COVID-19 pandemic. The purpose of this editorial is to briefly reflect on the importance of e-caring for leadership during the crisis and increase the commitment of nursing leaders to continue their great works even after the pandemic with an organizational culture infused with e-caring.